GENETIC PROGRAMMING FOR BRICK'S CHEMICAL ANALYSIS MODELLING - H., Marouf1*; A., . Semcha2; N, Mahmoudi3, Bouhamou1 N. (جامعة الوادي university of eloued, 2018)
This study is part of the search for a sediment management methodology and the basic material that is designed for the manufacture of fired brick, in which we tackle the problem of choosing the mud samples from dredging the Algerian dams in particular (Bouhanifia dam western Algeria) and the choice of clay that comes from different deposits. We propose an approach for sampling using a computer optimization model that allows solving and optimizing a characterization to retain the best adapted sample (chemically) using
artical
Keywords: Sludge- Dredging- Sample- Chemical Characterization- Brick-Optimization Methods- Genetic Algorithm